Study on Partial Discharge Detection of 10kV XLPE Power Cable - Zhang Weixia; Zhao Xianping; Zhao Shutao; Yu Hong; Wang Dada (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Partial discharge is a main factor which causes cross-linked polyethylene (XLPE) cable damaged. In order to research the Partial Discharge detecting methods of 10kV XLPE power cable, the electrostatic field is firstly simulated in order to analysis the electric filed at the distortion of the cable. According to the simulation mode, portable thermal infrared imager and ultraviolet imaging instrument is utilized to detect partial discharge of power cable terminals. The experimental results demonstrate that the use of ultraviolet imaging instrument to detect the location of defects is efficient and can observe corona photons; and thermal infrared imager can detect the temperature rising caused by Partial discharge. And this result also verified the simulation result that electric field concentration resulted in partial discharge. Test results also show that in short period of time partial discharge changes not much. This is mainly because the energy caused by PD does not accumulate so much in short time. That is contributing to the discovery of potential defects. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1577